2015
DOI: 10.1039/c4dt02422b
|View full text |Cite
|
Sign up to set email alerts
|

Radical anionic versus neutral 2,2′-bipyridyl coordination in uranium complexes supported by amide and ketimide ligands

Abstract: A series of 2,2′-bipyridyl uranium complexes shows that bipy is found as a radical anion or a neutral ligand such that uranium is in the +4 oxidation state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 52 publications
3
13
0
Order By: Relevance
“…The C py −C py distances of 1.425(4)–35(5) Å in 1 are clear‐cut and all within the 1.43 Å range established for the bipy .− anion and comparable to those found in [U IV [N( t Bu)Ar] 2 (bipy .− ) 2 ] (C py −C py =1.429(7), 1.426(7) Å) . Moreover, the NCCN dihedral angles in 1 range from 0.4–2.2°, consistent with the increased planarity that occurs within the bipy ligand upon one‐electron reduction .…”
Section: Methodssupporting
confidence: 76%
See 3 more Smart Citations
“…The C py −C py distances of 1.425(4)–35(5) Å in 1 are clear‐cut and all within the 1.43 Å range established for the bipy .− anion and comparable to those found in [U IV [N( t Bu)Ar] 2 (bipy .− ) 2 ] (C py −C py =1.429(7), 1.426(7) Å) . Moreover, the NCCN dihedral angles in 1 range from 0.4–2.2°, consistent with the increased planarity that occurs within the bipy ligand upon one‐electron reduction .…”
Section: Methodssupporting
confidence: 76%
“…The diagnostic, oxidation-stated ependentf !ft ransition bands of uranium are not visible in the UV/Vis/NIR spectra of 1 and 2.I nstead, in both spectra of 1 and 2,t hese bands are obscured by ac omparatively intense, broad absorption in the 600-1000 nm region with an accompanying band found between 300-400 nm, [16] signature features of the bipy À C p!p* transitions. [15] The magnetic properties of 1 and 2 werei nvestigated using aS QUID magnetometer.T he dc magnetic susceptibility measurements of 1 and 2 were performed on crushed polycrystal-line samples in the temperature range of 1.9-300 K, under an appliedd cf ield of 1000 Oe (Figure 3). The room temperature c M T value of 2.37 cm 3 Kmol À1 for 1 strongly suggests the presence of aU IV ion ( 3 H 4 , S = 1, L = 5) with four bipyC À radicals.…”
supporting
confidence: 79%
See 2 more Smart Citations
“…[14] Germane to this study Th IV complexes containing direduced 2,2′-bipy have been reported by Walter and Zi [15][16][17] and Arnold, [18] and uranium complexes containing mono-reduced 2,2′-bipy have been reported by Bart [19] and Cummins. [20] Two equivalents of 1 doubly reduce 4,4′-bipy and reductively couple two equivalents of pyridine to yield [{Th(Cp′′)3}2{µ-(NC5H4)2}] (2) and [{Th(Cp′′)3}2{µ-(NC5H5)2}] (3), respectively (Scheme 1). Although selected Ln II (Ln = Sm, Tm) [12c-e] and Sc III arene [21] complexes can reductively couple pyridine, Ephritikhine and co-workers have shown by single crystal XRD studies that the comparable U III complexes [U(Cp′)3] and [U(Cp t )3] (Cp t = {C5H4 t Bu}) do not reduce pyridine [14,22] or 4,4′-bipy.…”
mentioning
confidence: 99%